2003
DOI: 10.1002/ijc.10947
|View full text |Cite
|
Sign up to set email alerts
|

BACH1 517C→T transition impairs protein translocation to nucleus: A role in breast cancer susceptibility?

Abstract: Dear Sir,Recent predictions of risks of developing a complex disease based on common genetic variations using breast cancer as a model suggest that the construction and use of genetic-risk profiles may improve the efficacy of population-based programs of intervention. 1 However, the identification of genes, alleles or haplotypes predisposing to complex diseases including breast cancer has been difficult to accomplish, despite the existence of a significant proportion of familial cases of breast cancer that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Another study has indicated that the rare variant Arg173Cys (tSNP rs4988345) impairs protein translocation to the nucleus and might modify breast cancer susceptibility [17], [26]. Since the minor allele for this variant is very rare (MAF = 0.008) in CEPH samples, we have very limited power to confirm or refute this association using the case-control population in the current study.…”
Section: Discussionmentioning
confidence: 90%
“…Another study has indicated that the rare variant Arg173Cys (tSNP rs4988345) impairs protein translocation to the nucleus and might modify breast cancer susceptibility [17], [26]. Since the minor allele for this variant is very rare (MAF = 0.008) in CEPH samples, we have very limited power to confirm or refute this association using the case-control population in the current study.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have indicated that the rare BRIP1 variant rs4988345 (Arg173Cys) impairs protein translocation to the nucleus and may also modify breast cancer susceptibility (Lei and Vorechovsky, 2003;Song et al, 2007). Since the MAF for this variant is very low (0.0065) in the Chinese Han population, we had limited power to confirm or refute this association using the case-control population of the current study.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have analyzed potential associations between BRIP1 variants and breast cancer risk, either by mutation analysis or by genotyping, to select single nucleotide polymorphisms (SNPs) within the gene (Lei and Vorechovsky, 2003;Rutter et al, 2003;Sigurdson et al, 2004;Lewis et al, 2005;Garcia-Closas et al, 2006;Vahteristo et al, 2006). Although the rs2048718 (5ꞌ-untranslated region, UTR), rs4988345 (exon 15), and rs4986764 (exon 18) polymorphisms have been previously examined in the context of breast cancer, these genetic association studies have failed to produce consistent results (Luo et al, 2002;Lei and Vorechovsky, 2003;Song et al, 2007;Pabalan et al, 2013). Furthermore, several important SNPs, such as rs2048718, rs4986764, rs4986763, rs11079454, and rs7213430, have not been included in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, phosphorylation of the Ser990 residue triggers FANCJ interaction with BRCT domains of BRCA1, which is required for establishment of the G2 cell-cycle checkpoint response to DNA damage (Yu et al 2003). Proper localization of FANCJ to the nucleus is impaired by the c.517C [ T variant (p.Arg173Cys) (Lei et al 2003), which has been suggested to have an effect on breast cancer susceptibility. Furthermore, enzymatic activity of FANCJ was found defective in two patients with germline FANCJ coding sequence mutations who experienced early onset breast cancer (Cantor et al 2004).…”
Section: Introductionmentioning
confidence: 99%